Sosyal Medya Pazarlamasının Tüketici Satın Alma Kararlarına Etkisi - AYOUBI, Sayed Basir Ahmad; NAWEER, Mohammad (PEARSON JOURNAL, 2024)
This study investigates the impact of social media marketing on consumer buying behavior in Afghanistan. By analyzing responses from a structured questionnaire distributed among Afghan social media users, the research explores the influence of demographic factors, social media usage patterns, and specific marketing strategies. The findings reveal that social media marketing significantly affects consumer purchasing decisions, with younger consumers (ages 18-34) showing a higher susceptibility to marketing messages. Notably, 60% of respondents reported making purchases based on social media advertisements, indicating a strong positive influence. The study also highlights that the amount of time spent on social media correlates with increased likelihood of purchasing based on advertisements encountered online. Among the various types of social media content, promotions and discounts emerged as the most engaging and effective in driving consumer behavior, followed by product updates and user-generated content. Ethical considerations, such as data privacy and content authenticity, are emphasized as crucial factors in maintaining consumer trust and ensuring effective engagement. The research provides valuable insights for marketers aiming to optimize their social media strategies to better influence consumer buying behavior in Afghanistan. Future research is suggested to explore the long-term effects of social media marketing and the role of cultural and socio-economic factors in shaping consumer responses.